G and P Genotypes of Group A Rotavirus in Diarrheic Calves in Costa Rica - Bonilla Espinoza, José (2021)
Rotavirus infections are the most common causes of infectious diarrhea in young children and animals worldwide. We performed a genotyping of rotavirus strains by RT-PCR for G (VP7) and P (VP4), in diarrhea samples from calves, in several locations in Costa Rica. Combinations of genotypes G (VP7) and P (VP4) were identified in cattle: 4 (26%) corresponding to G8 P [11], 4 (24%) to G6P [11], 3 (19%) to G8P [7], 2 (13%) to G10P [1], 3 (19%) to G10P [11], and 1 (6%) to G8P [1] and mixed infections. This research represents the first report of bovine rotavirus strains (calves) in Costa Rica and in the Central American region.